Islamic Economic Contribution In National Economic Development - Nuryenda Pinta Tarigan; Edwinsyah P Pohan (Proceeding International Seminar of Islamic Studies, 2019)
For a long time, humanity has been looking for systems to improve welfare, especially in the economic field. So far, there have been several systems, including two major flows in the economic system known in the world, namely the economic system of Capitalism (Adam Smith) and Socialism (Karl Mark). But in both of these systems no one succeeded in offering an optimal solution. Consequently people began to think of looking for alternatives. The alternative that is believed and promising by many is the Islamic economic system, because this system is based on the principles of justice and humanity. The presence of Islamic economics, of course, must be able to answer the problem. Islamic economics is not a new discourse in the social and scientific world. Islamic economics is a reality that continues to present itself to perfection amidst the diversity of conventional social and economic systems based on secular materialism. Islamic economics is also a scientific reality which always shows itself among the constellations of social sciences based on secularism and even atheism. The development of the national economy leads to the welfare of society if welfare is manifested in an increase in high income per capita, then modern capitalists will get the maximum number.